2020
DOI: 10.1136/bmj.m3499
|View full text |Cite
|
Sign up to set email alerts
|

How effective are clinical decision support systems?

Abstract: Current performance is disappointing, we should change direction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“… 167 , 168 Nevertheless, such approaches depend on integration of a much wider variety of EHR data types than what is currently used; requires ongoing work toward technological standards, 168–170 and needs greater subject matter expertise collaboration across clinical specialties. 149 , 171 Secondly, we echo previous authors in recommending that CDS evaluations include sufficient details of the CDS technology itself. 8 , 44 “Clinical decision support” is a broad term.…”
Section: Discussionsupporting
confidence: 59%
“… 167 , 168 Nevertheless, such approaches depend on integration of a much wider variety of EHR data types than what is currently used; requires ongoing work toward technological standards, 168–170 and needs greater subject matter expertise collaboration across clinical specialties. 149 , 171 Secondly, we echo previous authors in recommending that CDS evaluations include sufficient details of the CDS technology itself. 8 , 44 “Clinical decision support” is a broad term.…”
Section: Discussionsupporting
confidence: 59%
“…These systems may be integrated into provider electronic health records, accessed through the Internet, or delivered through mobile devices, and have a range of functions including providing point-of-care clinical prediction rules, highlighting guideline-supported management, optimizing drug ordering and documentation, and discouraging potentially harmful practices [2]. While CDSSs are widely considered to be an indispensable knowledge translation tool across care settings [3,4], existing systematic reviews have demonstrated only small to moderate improvements in the care processes that they target, and even less promising effects on clinical outcomes [2,5]. This has led to further research seeking to identify and establish specific features or "active ingredients" of CDSSs that might predict intervention success [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The need for high value care with minimal cost while maintaining the standards calls for clinical decision support systems that can intelligently channel our resources to people in low resource settings. [68].…”
Section: Discussionmentioning
confidence: 99%